2017
DOI: 10.1038/s41598-017-09557-8
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of phytase transgenic and non-transgenic maize seeds

Abstract: Proteomics has become a powerful technique for investigating unintended effects in genetically modified crops. In this study, we performed a comparative proteomics of the seeds of phytase-transgenic (PT) and non-transgenic (NT) maize using 2-DE and iTRAQ techniques. A total of 148 differentially expressed proteins (DEPs), including 106 down-regulated and 42 up-regulated proteins in PT, were identified. Of these proteins, 32 were identified through 2-DE and 116 were generated by iTRAQ. It is noteworthy that onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…Recently, the second-generation proteomic technique iTRAQ has been widely used in comparative proteomic analyses because of its accuracy and reliability 1820 . However, 2-DE has advantages, and many highly abundant unique proteins can be easily detected by both 2-DE and iTRAQ techniques 21 . Therefore, the 2DE and iTRAQ approaches currently represent two major techniques used in comparative proteomics 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the second-generation proteomic technique iTRAQ has been widely used in comparative proteomic analyses because of its accuracy and reliability 1820 . However, 2-DE has advantages, and many highly abundant unique proteins can be easily detected by both 2-DE and iTRAQ techniques 21 . Therefore, the 2DE and iTRAQ approaches currently represent two major techniques used in comparative proteomics 22 .…”
Section: Introductionmentioning
confidence: 99%
“…We compared the proteomics of leaves between the phytase- transgenic (PT) maize and a nontransgenic (NT) isogenic variety via using a routine 2-DE and MS-based method 30 . Recently, we also used both 2-DE-MS/MS and iTRAQ-based methods to identify the quantitative proteomic differences between PT and NT maize seeds grown in a greenhouse 21 . Some differentially accumulated proteins (DAPs) were detected, but the proteomic patterns were not substantially different between PT maize and the NT type.…”
Section: Introductionmentioning
confidence: 99%
“…Neighboring inside the BL is an endosperm tissue called BETL, and outside is a pericarp IEP. The proteome of whole maize seeds, embryos, and endosperm has been intensively investigated in recent decades [23,25,[38][39][40][41][42][43][44]. Due to the difficulty of separating tissues from kernels, the proteome for some targeted seed parts has seldom been the focus, except for BETL, whose functions have been implied to mediate embryo-endosperm interactions and play a role in plant defense by this method [45][46][47][48] To date, no attempt has been focused on BL, and very little is known about its developmental processes, as well as the physiological and molecular roles of this tissue in kernel development.…”
Section: Discussionmentioning
confidence: 99%
“…The result demonstrated that the heterologous expression of ferritin and phytase in crops could contribute to an increase in iron bioavailability and absorption, especially in cereal-based diets that more or less lack some trace elements (Drakakaki et al, 2005 ). It is worth noting that proteomic analysis of phytase transgenic corn seeds showed that some ribosomal proteins and heat-shock proteins might present adaptive effects in response to the insertion of Aspergillus phytase phyA2 (Tan et al, 2017 ). Three ways have been proposed to increase the accumulation of iron in rice grains.…”
Section: Microelements and Their Genetic Regulation Via Transgenic Apmentioning
confidence: 99%